A revision of the taxonomy of Dendrelaphis caudolineatus (Gray, 1834) (Serpentes: Colubridae) - van Rooijen, Johan; Vogel, Gernot (Zootaxa, 2012)
The systematics of the wide-ranging southeast Asian colubrid snake Dendrelaphis caudolineatus (Gray, 1834) wasinvestigated on the basis of multivariate analyses of morphological and coloration data for 131 museum specimensrepresenting 28 geographically isolated populations. The results demonstrate that the current taxonomy of D.caudolineatus underestimates species diversity in the Philippines. The following revisions are implemented. 1)Populations from the Philippine island Palawan and adjacent islands currently referred to D. c. caudolineatus (Gray, 1834)are described as a new species, D. levitoni sp. nov. 2) Populations from the Philippine islands Negros, Panay, Mindoroand Masbate, currently assigned to D. c. terrificus (Peters, 1872) and D. c. luzonensis Leviton, 1961 are referred to D.fuliginosus Griffin 1909, which is revalidated. 3) Populations from the southern Philippine islands Basilan, Mindanao,Cebu, Bohol, Leyte, Samar, Polillo, Kalotkot, Catanduanes as well as Southeast Luzon currently referred to D. c. terrificus(Peters, 1872) are referred to D. philippinensis Günther, 1879 which is revalidated. 4) The population from Sulawesi isreferred to D. terrificus (Peters, 1872). Currently regarded as a polytypic species composed of five subspecies, D.caudolineatus is here considered to be a monophyletic group comprising eight species. The distributions of these eightspecies correspond largely with aggregate island complexes formed during periods of reduced sea level during the Pleistocene. However, some deviations indicate post-Pleistocene dispersals across sea barriers.